2023
DOI: 10.1111/bcpt.13925
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing in primary care without deterioration of health‐related outcomes: A real‐life, quality improvement project

Abstract: Medication reviews focusing on deprescribing can reduce potentially inappropriate medication; however, evidence regarding effects on health‐related outcomes is sparse. In a real‐life quality improvement project using a newly developed chronic care model, we investigated how a general practitioner‐led medication review intervention focusing on deprescribing affected health‐related outcomes. We performed a before–after intervention study including care home residents and community‐dwelling patients affiliated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the decision making process becomes complicated by the inherent variability of patient responses to medications. 7 Whilst one patient might thrive without a certain medication, another might deteriorate, complicating predications about clinical outcomes. Beyond this, a clinician must also seek to understand and negotiate the patient's beliefs and values about their health, and must seek to collaborate with the patient on a decision.…”
mentioning
confidence: 99%
“…Furthermore, the decision making process becomes complicated by the inherent variability of patient responses to medications. 7 Whilst one patient might thrive without a certain medication, another might deteriorate, complicating predications about clinical outcomes. Beyond this, a clinician must also seek to understand and negotiate the patient's beliefs and values about their health, and must seek to collaborate with the patient on a decision.…”
mentioning
confidence: 99%
“…Baas et al 13 report a process evaluation of a medication review intervention aimed at deprescribing cardiometabolic medications for patients with type 2 diabetes. Olesen et al 14 describe a deprescribing quality improvement study in Danish general practice, which improved patient self‐reported health status. Shrestha et al 15 present development of a deprescribing tool for older people with limited life expectancy.…”
mentioning
confidence: 99%